2013
DOI: 10.18352/lq.8082
|View full text |Cite
|
Sign up to set email alerts
|

Data Management in Scholarly Journals and Possible Roles for Libraries – Some Insights from EDaWaX

Abstract: In this paper we summarize the findings of an empirical study conducted by the EDaWaX-Project. 141 economics journals were examined regarding the quality and extent of data availability policies that should support replications of published empirical results in economics. This paper suggests criteria for such policies that aim to facilitate replications. These criteria were also used for analysing the data availability policies we found in our sample and to identify best practices for data policies of scholarl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
0
13
0
3
Order By: Relevance
“…They may require assistance with activities such as creating metadata, locating datasets, and finding appropriate places to store their data (Aydinoglu, Suomela, & Malone, 2014;Enke et al, 2012;Kratz & Strasser, 2015;Schmidt, Gemeinholzer, & Treloar, 2016;Specht et al, 2015;Tenopir et al, 2011Tenopir et al, , 2015a. Earlier surveys of researchers suggest roles for research libraries in providing support for research data management, an extension of the library's traditional role in providing research and reference services (Si et al, 2015;Tenopir et al, 2012Tenopir et al, , 2015bVlaeminck, 2013).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They may require assistance with activities such as creating metadata, locating datasets, and finding appropriate places to store their data (Aydinoglu, Suomela, & Malone, 2014;Enke et al, 2012;Kratz & Strasser, 2015;Schmidt, Gemeinholzer, & Treloar, 2016;Specht et al, 2015;Tenopir et al, 2011Tenopir et al, , 2015a. Earlier surveys of researchers suggest roles for research libraries in providing support for research data management, an extension of the library's traditional role in providing research and reference services (Si et al, 2015;Tenopir et al, 2012Tenopir et al, , 2015bVlaeminck, 2013).…”
Section: Related Workmentioning
confidence: 99%
“…Research data services (RDS) provided by libraries vary and may include: creation and management of institutional data repositories, providing tools for data mining and visualization, training for researchers on data management activities, guidance on institutional policies, help with creating data management plans and metadata for data sets, and assistance with intellectual property and privacy issues surrounding research data, and other services (Flores, Brodeur, Daniels, Nichalls, & Turnator, 2015;Koltay, 2016;Linde, Noorman, Wessels, & Sveinsdottir, 2014;Tenopir et al, 2012Tenopir et al, , 2015bVlaeminck, 2013).…”
Section: Related Workmentioning
confidence: 99%
“…In the field of economics, building on the work of US economist B. D. McCullough, Vlaeminck (2013) found that out of 141 journals, 20.6 per cent had a data availability policy (only one of these was OA) and even fewer (7.8 per cent) had a replication policy. 19 In addition to studying the extent of such policies, Vlaeminck also looked at the quality of the available policies.…”
mentioning
confidence: 99%
“…19 In addition to studying the extent of such policies, Vlaeminck also looked at the quality of the available policies. The author found that the majority of journals with policies had one similar to journals published by the American Economic Association; those journals make data submission mandatory (whenever possible) and specify what data and files should be submitted to the journal prior to publication.…”
mentioning
confidence: 99%
“…• Few social science journals have currently implemented guidelines requiring their authors to provide their data and statistical computation codes (McCullough, 2009;Vlaeminck, 2013). So called "data availability policies" may, in some instances, oblige the authors of empirical research papers to supply the underlying data of their results and the code/syntax of their analysis along with the manuscript of the article.…”
mentioning
confidence: 99%